Nonverbal Communication as a Symbol of Love in Long Distance Relationship (LDR) - Manap, Solihat; Michelle, Kezia Onggowidjaja (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Communication is a form of interaction that humans do in conveying various forms of messages both verbally and nonverbally. In some cases, such as describing the expression of love and affection towards a partner, humans use nonverbal communication. Research on nonverbal communication as a symbol of love for long-distance partners in the midst of the COVID-19 pandemic was carried out using descriptive qualitative research methods. Data were obtained through in-depth interviews using a purposive sampling technique. There were 5 informants. The data analysis process went through the data collection stages. data reduction, data display and conclusions.. The results show that the classification of nonverbal messages in sign language can be represented by the use of emojis when exchanging messages. Furthermore, the language of action can be represented by how couples communicating while in their long distance relationship like exchanging messages, video calling, and so on. Finally, object language can be represented by giving surprises or gifts, exchanging photos, and so on. The conclusion of nonverbal communication as a symbol of affection for long-distance partners can be represented by 3 classifications of nonverbal messages, namely sign language, action language, and object language. The advice given can always maintain the warmth of the relationship even though you are in the middle of a long-distance relationship and better understand each other's love language.